Phytoplankton Composition and Water Quality of Kwan Phayao Reservoir, Thailand, during Rainy and Cold Dry Seasons - Ngearnpat, Neti; Klayluk, Bawornrat; Kumla, Aumnaj; Ngamta, Saowanee; Issakul, Kritchaya (Journal of Food Health and Bioenvironmental Science, 2018)
This research investigates the phytoplankton composition and water quality of Kwan Phayao Reservoir, Thailand, during rainy and cold dry seasons. From the results, 6 Divisions with 90 species of phytoplankton were observed for both seasons. Among them, Chlorophyta is the most dominant group, followed by Bacillariophyta and Cyanophyta. Microcystis aeruginosa is the dominant phytoplankton species in both seasons accounting for the total amount of 82.14 and 78.86% for the rainy and cold dry seasons, respectively. Shannon’s diversity index (H’) and evenness (J) were 0.9 and 0.22 in the rainy season, and 1.14 and 0.30 in the cold dry season. Based on the physicochemical and biological parameters, nitrate nitrogen, phosphate, DO and BOD tended to decrease in the cold dry season. While, the conductivity and total coliform bacteria were higher in the cold dry than the rainy season. The canonical correspondence analysis (CCA) results indicate that the distribution and abundance of Lyngbya sp., Spondylosium sp., Ankistrodesmus sp., Merismopedia sp., Crucigeniella sp., Cylindrocystis sp., Micractinium sp., Spirulina sp., Monoraphidium sp., Gonatozygon sp. and Volvox sp. are related to the Secchi depth, water depth, pH, chlorophyll-a, air and water temperatures, DO, BOD, phosphate and nitrate in the rainy season. While, during the cold dry season, the distribution of Strombomonas sp., Cyanobacterium sp. and Didymocystis sp. are related to the conductivity, turbidity, ammonia nitrogen and total coliform bacteria. This research results indicate that the relationship between phytoplankton community and water quality of Kwan Phayao Reservoir are affected by climatic and seasonal changes.